From Biological to Cultural Perspectives: Reframing Primate Conservation through Ethnoprimatology in Indonesia — A Literature Review - Tresno; Vivienne Loke Pei Wen; Femei Rahmilija; Deni Aries Kurniawan; Ilal Ilham; Aldri Oktanedi (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2025)
Conservation in Indonesia has focused on biological indicators such as population decline and habitat loss, often overlooking the cultural dimensions that shape human–primate relationships. This study aims to integrate biological and cultural perspectives by applying an ethnoprimatological approach to reframe primate conservation. A qualitative literature review of publications from 2000 to 2025 was conducted using Google Scholar with the keywords “ethnoprimatology” and “human–primate interaction”. Thirty-four studies met the inclusion criteria and were analyzed thematically within a multispecies ethnography framework. The findings reveal diverse cultural meanings attributed to primates across Indonesia: in Bali, Sulawesi, and Sumatra, primates are simultaneously revered as sacred beings and perceived as agricultural pests; in Kalimantan, Jambi, and Mentawai, they are hunted for subsistence or ritual offerings; and in West Sumatra and Java, they are domesticated and trained for labor or performance, reflecting economic integration. These cultural interpretations shape community attitudes more strongly than biological conservation status. The study concludes that effective primate conservation requires incorporating cultural taxonomies to develop strategies that are both culturally grounded and ecologically sustainable.